Validation of a wireless communication protocol to monitor human gait using IMUs - Ribeiro, Nuno Ferrete (2017)
Ambient Assisted Living (AAL) represents a very relevant area of study since it is of great interest to monitor not only people in need of treatment or rehabilitation, but also healthy and elderly people. One of the main necessities is to monitor the human gait. However, there are still some open issues to be addressed. Namely, the literature shows that there are differences between indoor and outdoor environments. Thus, within the framework of a project to monitor human gait using IMUs (Inertial Measurement Units, MPU-6000 Motion Processing Units), the Enhanced Low Power Real Time (eLPRT) protocol was validated by obtaining the percentage of lost packets (lost protocol messages that contain inertial/magnetic sensors information). Concerning the system, the IMUs were connected to a base station (SmartRF05EB) by means of Radio Frequency (RF). This base station was connected to a personal computer to process the data in real time. In order to validate the communication protocol, the losses of data packets were accounted for during the trials carried out by one subject in three different environments: i) inside a laboratory; ii) in a corridor; and iii) in an outdoor environment. As results, the range of average percentage of loss was 0.52% to 15.21% inside the laboratory; 1.15% to 8.93% in the corridor; and 0.90% to 7.51% in the outdoor environment depending on the number of sensor modules used and subject pace speed. The absence of ferromagnetic materials and other wireless communications with the same frequency band are the main reasons why the RF transmission had better performance in an outdoor environment.